Respuesta :

Answer:

The inverse is

[tex]y =\sqrt{\frac{(\frac{x-3}{3}) ^{2}+5}{2}}[/tex]

Step-by-step explanation:

[tex]y=3\sqrt{2x^{2} -5} + 3[/tex]

To find the inverse of the function interchange the terms that's x becomes y and y becomes x

We have

[tex]x=3\sqrt{2y^{2}-5 }+3[/tex]

Now solve for y

Move 3 to the other side of the equation

[tex]3\sqrt{2y^{2}-5 } = x-3[/tex]

Divide both sides by 3

We have

[tex]\sqrt{2y^{2}-5 } =\frac{x-3}{3}[/tex]

square both sides of the equation to remove the square root

That's

[tex]2y^{2}-5 = (\frac{x-3}{3}) ^{2}[/tex]

Move 5 to the other side of the equation

[tex]2y^{2} = (\frac{x-3}{3}) ^{2}+5[/tex]

Divide both sides by 2

We have

[tex]y^{2} = \frac{(\frac{x-3}{3}) ^{2}+5}{2}[/tex]

Find the square root of both sides

We have the final answer as

[tex]y =\sqrt{\frac{(\frac{x-3}{3}) ^{2}+5}{2}}[/tex]

Hope this helps you